PRAKTIK FIKIH KESEHARIAN MINORITAS MUSLIM DI BALI - fathor rahman (Jurnal Studi Agama dan Masyarakat, 2020)
This paper explored a daily fiqh practice or, more precisely, the practice of Islam among Muslim minorities in Bali, which is transformed into an adaptable form of religious diversity promoting harmony. In the midst of the strong domination of Hindu custom and the acts of violence by few Muslims in Indonesia, the Balinese Muslim community strived to manifest Islamic teachings (fiqh) in daily life having tolerant and moderate. Through two problems such as; how is the religious adaptation pattern of minority Muslim communities in Bali? How do Muslim communities establish inter-religious harmony as a manifestation of their daily fiqh? This study attempted  to analyze it based on maqashid sharia theory. As for supporting data collection, this paper used field research using interviews and observations.The finding  indicated that there were interesting patterns of religious social relations occurred in the daily practice of Muslim minorities in expressing their Islamic teachings in the public area. Muslims in Bali are able to appraise their religious teachings and adapt with the surrounding community, which was socio-anthropologically dominated by the Hindu belief system.